Pengetahuan ibu tentang mobilisasi dini pasca persalinan normal pervaginam di Wilayah Kerja Puskesmas Labuhan Rasoki Kecamatan Padangsidimpuan Tenggara Tahun 2018 - Dewi, Sri Sartika Sari; Batubara, Novita Sari (Universitas Aufa Royhan, 2018)
The period of postpartum(puerperal)is a time to recover, from the delivery finished up tools such as pre-pregnant uterus back. The postpartum period lasts for ± 6 weeks. One of the treatments for postpartum mothers is early mobilization. During early childbirth the mother is allowed to stand and walk around. The study design was descriptive, namely to identify maternal knowledge about early vaginal postpartum mobilization. The study was carried out in the Labuhan Rasoki Community Health Center in Padangsidimpuan Southeast District. The study population was all mothers who had vaginal births during the period of June 2017 to January 2018 as many as 124 people. The sampling technique uses a approach that is simple random sampling simple random sampling , the number of study samples is 95 people. Descriptive data of respondents age were obtained by the majority of 25-30 years old, namely 46 people (48.4%) and minority <25 years old, 22 people (23.2%). The majority of respondents had a basic education of 42 people (44.2%) and a minority who did not go to school, namely 2 people (2.1%). The majority of respondents work, namely 60 people (63.2%) and the minority does not work, 35 people (36.8%). The majority of respondents received information from health workers, namely 43 people (45.3%) and minorities obtained information from relatives or family, namely 25 people (26.3%). The majority of secundipararespondents were 37 people (38.9%) and multipara minorities which were 27 people (28.4%). Based on the results of this study, it can be concluded that generally maternal knowledge about early vaginal postpartum mobilization in Labuan Rasoki Health Center Working Area South Padangsidimpuan Sub District in 2018 is in the good category of 83 people (87.4%) and 12 minority categories (12 , 6%). It is recommended to health workers to apply early mobilization after vaginal vaginal delivery in postpartum maternal care.